Money markets, collateral and monetary policy - Fiorella De Fiore; Marie Hoerova; Harald Uhlig (European Central Bank (ECB), 2019)
Interbank money markets have been subject to substantial impairments in the recent decade, such as a decline in unsecured lending and substantial increases in haircuts on posted collateral. This paper seeks to understand the implications of these developments for the broader economy and monetary policy. To that end, we develop a novel general equilibrium model featuring heterogeneous banks, interbank markets for both secured and unsecured credit, and a central bank. The model features a number of occasionally binding constraints. The interactions between these constraints - in particular leverage and liquidity constraints - are key in determining macroeconomic outcomes. We find that both secured and unsecured money market frictions force banks to either divert resources into unproductive but liquid assets or to de-lever, which leads to less lending and output. If the liquidity constraint is very tight, the leverage constraint may turn slack. In this case, there are large declines in lending and output. We show how central bank policies which increase the size of the central bank balance sheet can attenuate this decline.
Keywords: G10; G20; E44; E52; E58; 330; Money markets; Liquidity; Collateral; Monetary policy; Interbankenmarkt; Geldmarkt; Liquiditätsbeschränkung; Kreditderivat; Geldpolitik; Theorie